One‐pot Three Component Synthesis of ω‐(oxathiolan‐2‐thion‐5‐yl)‐α‐oxazolidin‐2‐ones. (21st March 2017) - Ghrab, Saad; Aroua, Lotfi; Beji, Mohamed
Abstract : We report a practical and one‐pot synthesis of novel series of ω‐(oxathiolan‐2‐thione‐5‐yl)‐α‐ oxazolidin‐2‐ones (3a‐h ). The obtained compounds have been designed, synthesized via reaction of oligoethylene glycols diglycidyl ethers, isocyanate and carbon disulfide in the presence of catalytic amount of lithium bromide. A variety of important oxazolidinone derivatives can be obtained from simple starting materials in good yields and the biological activity of these new products will be investigated in complementary study. Abstract :